Visualizing evolution in real-time method for strain engineering - Reyes, Luis H.; Winkler, James; Kao, Katy C. (Frontiers in Microbiology, 2012)
The adaptive landscape for an industrially-relevant phenotype is determined by the effects of the genetic determinants on the fitness of the microbial system. Identifying the underlying adaptive landscape for a particular phenotype of interest will greatly enhance our abilities to engineer more robust microbial strains. Visualizing evolution in real-time (VERT) is a recently developed method based on in vitro adaptive evolution that facilitates the identification of fitter mutants throughout the course of evolution. Combined with high-throughput genomic tools, VERT can greatly enhance the mapping of adaptive landscapes of industrially-relevant phenotypes in microbial systems, thereby expanding our knowledge on the parameters that can be used for strain engineering.